The Satisfaction of Higher Education Students with Sex Education Training: A Cross-Sectional Study - Ana Frias; Maria da Luz Barros; Florbela Bia; Conceição Santiago; Açucena Guerra; Sagrario Gómez-Cantarino; Monica Raquel Pereira-Afonso; Daniela Mecugni; Vicki Aaberg; Fátima Frade (Education Sciences)
To maximize the potential of sex education, it is essential to optimize aspects related to the environment, the trainer–trainee interaction, and the quality of training. The objective of the present study was to identify and describe the satisfaction of higher education students with sex education training. An exploratory, descriptive, and cross-sectional study was carried out using the Student Satisfaction with Higher Education questionnaire, which was applied to a sample of 132 higher education students from several countries. In the statistical analysis using the SPSS software version 28, non-parametric tests were used, namely, the Mann–Whitney test and the Kruskal–Wallis test, in addition to Spearman’s correlation coefficient. Overall, the participants considered themselves very satisfied with the sex education training provided (χ = 4.77). The largest contribution to the satisfaction of the higher education students with the sex education training was the “quality of the training organization (environment and content)” (χ = 4.79). Educators and policymakers have the role of designing, implementing, and evaluating programs that satisfy college students and encourage them to strive for more sex education training aimed at promoting well-being, happiness, and sexual health.